P325 Inadequate inhibition of platelet function after exercise in patients with ischemic mitral regurgitation qualified for cardiosurgery treatment. (17th January 2020) - Piatkowski, R; Kochanowski, J; Budnik, M; Huczek, Z; Scislo, P; Kosior, D A; Opolski, G
Abstract: Purpose: Human platelets play a major role in the pathophysiology of cardiovascular diseases. The aim of our study was to determine the relationship between exercise and level of platelet inhibition in patients (pts) after myocardial infarction (MI) with at least moderate ischemic mitral regurgitation (IMR) qualified for cardiosurgical treatment - coronary artery bypass grafting alone (CABG) or CABG with mitral reconstruction (CABGmr). Methods: We collected venous blood samples from 70 pts (M 41, 66 ± 9 years) with at least moderate IMR, 3-24 weeks after MI. Platelet reactivity was estimated with the use of rapid, point-of-care platelet analyzer as the time for flowing whole blood to occlude a collagen-epinephrine ring, with shorter closure times (CEPI-CT), indicating greater activity. CEPI-CT was evaluated before (CEPI-CT rest) and 20 min after ExE (CEPI-CT ExE). Inadequate inhibition of the TXA2-dependent activation pathway was defined as CEPI-CT < 193 seconds. All the patients received 75-100 mg of aspirin daily (without clopidogrel treatment). Effective regurgitation orifice (ERO) was used for quantitative IMR assessment (moderate ≥10-20, severe ≥ 20 mm²). In all pts symptom-limited echocardiography (echo) semi-supine exercise test (ExE) was performed with Schiller system. All the pts were referred for CABG (multivessel coronary disease, ejection fraction (EF) 42, 6 ± 10, 1%, wall motion score index (WMSI) 1.65 ± 0.36). Results: We observed inadequate platelet in 26 (37%) pts at rest (CEPI-CT < 193 sec., despite regular aspirin therapy) and in 48 (68%) pts in 20 min. after exercise. We observed a significant decrease in CEPI–CT in all analyzed group (rest vs exe: 202 sec. vs 124 sec., respectively; p < 0, 0001) and also in pts with moderate IMR as well as with severe IMR. We didn't observe a significant change in platelet count and mean platelet volume (MPV) between rest and exercise. Conclusions: 1. Inadequate antiplatelet effect of aspirin at rest was observed in 37% pts after MI with IMR. 2. Symptoms limited exercise test has revealed inadequate platelet inhibition (TXA2 –dependent activation pathway) in 68% of patients after MI with IMR. 3. Aspirin may have a limited antithrombotic effect after physical exercise in patients after MI with significant IMR.